Regulatory T Cell-Related Gene Indicators in Pulmonary Hypertension - Liu, Yan; Shi, Jun-Zhuo; Jiang, Rong; Liu, Shao-Fei; He, Yang-Yang; van der Vorst, Emiel P. C.; Weber, Christian; Döring, Yvonne; Yan, Yi (Frontiers in Pharmacology, 2022)
Objective: Regulatory T cells (Tregs) are critical immune modulators to maintain immune homeostasis and limit pulmonary hypertension (PH). This study was aimed to identify Tregs related genes (TRGs) in PH. Methods: The gene expression profile from lungs of PH patients were retrieved from Gene Expression Omnibus (GEO) database. The abundance of Tregs was estimated by the xCell algorithm, the correlation of which with differetially expressed genes (DEGs) was performed. DEGs with a |Pearson correlation coefficient| > 0.4 were identified as TRGs. Functional annotation and the protein-protein interaction (PPI) network were analyzed. A gene signature for 25 hub TRGs (TRGscore) was generated by single sample scoring method to determine its accuracy to distinguish PH from control subjects. TRGs were validated in datasets of transcriptional profiling of PH cohorts and in lung tissues of experimental PH mice. Results: A total of 819 DEGs were identified in lungs of 58 PAH patients compared to that of 25 control subjects of dataset GSE117261. 165 of all these DEGs were correlated with the abundance of Tregs and identified as TRGs, with 90 genes upregulated and 75 downregulated compared to that of control subjects. The upregulated TRGs were enriched in negative regulation of multiple pathways such as cAMP-mediated siganling and I-kappaB kinase/NF-kappaB signaling, and regulated by multiple genes encoding transcriptional factors including HIF1A. Furthermore, 25 hub genes categorized into 3 clusters out of 165 TRGs were derived, and we identified 27 potential drugs targeting 10 hub TRGs. The TRGscore based on 25 hub TRGs was higher in PH patients and could distinguish PH from control subjects (All AUC > 0.7). Among them 10 genes including NCF2, MNDA/Ifi211, HCK, FGR, CSF3R, AQP9, S100A8, G6PD/G6pdx, PGD and TXNRD1 were significantly reduced in lungs of severe PH patients of dataset GSE24988 as well as in lungs of hypoxic PH mice compared to corresponding controls. Conclusions: Our finding will shed some light on the Tregs-associated therapeutic targets in the progression of PH and emphasize on TRGscore as a novel indicator for PH.